Graphical model based spatio-temporal modeling of extreme events - Zhang, Liaofan (2013)
A novel model is proposed in this thesis to describe in a flexible manner the extreme events in both spatial and temporal domain. This model can be used to model the occurrence of extreme events in different places and at different times.